Fonctionnement Et Dysfonctionnement - Badaoui, Fouzia; Boumaraf, Assia (جامعة الوادي - University of Eloued, 2020)
ملخص: الهدف من هذا البحث هو عرض نظرية لغوية تتبنى تحليل الاضطرابات اللغوية وهي نظرية الوساطة التي جاء بها جانيوبان. سوف نسلط الضوء على طرق استغلال هذه النظرية في مجال الاضطرابات اللغوية بما في ذلك مجال فقدان القدرة على الكلام. سنقدم ملخصًا لمختلف اللنماذج التحليلية في نظرية الوساطة، ثم نقوم بتحليل النموذج اللساني ومختلف أوجه تحليله، وسنختم بعرض العلاقة بين النظرية اللغوية والفحص العيادي، وطريقة تحليل المعطيات اللسانية. . Abstract: The objective of this research is the presentation of a linguistic theory that refers to the analysis of pathological language namely the theory of mediation developed by J.Gagnepain, We highlight the mediation theory’ methods of exploitation in the domain of pathological language including aphasia. We will present a summary of the different models of analysis in the theory of mediation, then we will describe the linguistic model and its different glossological analysis, we end with the presentation of the relationship between linguistic theory and clinical observation of linguistic facts.
مقال
Keywords: Linguistic model; mediation theory; aphasia; clinical domain; Modèle linguistique; théorie de la médiation; aphasie; domaine clinique